The use of medical claims to assess incidence, diagnostic procedures and initial treatment of myelodysplastic syndromes and chronic myelomonocytic leukemia in the Netherlands. Issue 2 (February 2015) - Dinmohamed, Avinash G.; van Norden, Yvette; Visser, Otto; Posthuma, Eduardus F.M.; Huijgens, Peter C.; Sonneveld, Pieter; van de Loosdrecht, Arjan A.; Jongen-Lavrencic, Mojca
Highlights The age-standardized incidence rate (ASR) per 100, 000 was 5.4 for MDS and 0.4 for CMML. The ASR of MDS was almost 2-fold higher than in the Netherlands Cancer Registry (NCR). Almost half of all cases were diagnosed without a bone marrow examination (BM). The ASR in the MDS cohort with BM examinations was comparable with the NCR. The majority of patients, either with or without BM examinations, received no therapy.